The influence of the organization structure changes on management and sports results in the Lech Poznan sports club between 2011 and 2014 - ŁUKASZ KARSKI (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: The increase in the competitiveness on the sports market forces elaboration of the proper organization structure in sports clubs. In 2011 Lech Poznan Club found itself in a situation which was inadequate to its ambition. The aim of this work is to present the influence of the implemented organization structure changes on the process of club management. Material and methods: The subject of the research was the Lech Poznan club and its organization structure between 2011 and 2014. The applied research methods were the interview and the survey questionnaire. Results: The introduction and the strategy realization, as well as the clear distribution of tasks were visible in the process of the changes in the organization structures. The success of those actions may be verified on the basis of the results of the end of season 2014/15. Conclusions: The conducted research shows that the Lech Poznan football club experienced transformation between 2011 and 2014. This transformation was adequate to the current trends of the sports club management, and it has permitted the club to win the Polish football championship.